2021
DOI: 10.1101/2021.07.14.452376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional enrichment of alternative splicing events with NEASE reveals insights into tissue identity and diseases

Abstract: Alternative splicing (AS) is an important aspect of gene regulation. Nevertheless, its role in molecular processes and pathobiology is far from understood. A roadblock is that tools for the functional analysis of AS-set events are lacking. To mitigate this, we developed NEASE, a tool integrating pathways with protein-protein and domain-domain interactions to functionally characterize AS events. We show in four application cases how NEASE can identify pathways contributing to tissue identity and cell type devel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…In fact, not all AS events have functional relevance, therefore, identifying the meaningful changes in the protein structure and protein-protein interactions caused by spliced exons will provide important biological insights into individual AS events or isoform switches. We took advantage of NEASE [21], a bioinformatics tool integrating pathways with structural annotations of protein-protein interactions for human genes, to functionally characterize AS events in the human transcriptomes. Using RNAseq data of human embryonic stem cells at seven early neural differentiation time points (0-72 h) [34], we demonstrated that NEASE can reveal the functional impact of spliced exons, which are complementary to the gene-level enrichment analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, not all AS events have functional relevance, therefore, identifying the meaningful changes in the protein structure and protein-protein interactions caused by spliced exons will provide important biological insights into individual AS events or isoform switches. We took advantage of NEASE [21], a bioinformatics tool integrating pathways with structural annotations of protein-protein interactions for human genes, to functionally characterize AS events in the human transcriptomes. Using RNAseq data of human embryonic stem cells at seven early neural differentiation time points (0-72 h) [34], we demonstrated that NEASE can reveal the functional impact of spliced exons, which are complementary to the gene-level enrichment analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Even though various computational tools have been developed to quantify transcript isoforms and identify splicing events [20][21][22][23][24], functional characterization of AS events has proven to be challenging. Gene-level enrichment analyses such as GO, KEGG, and GSEA generally focus on differential AS genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With temporal patterns of the clusters, Spycone dissects context-specific processes in terms of AS. In order to gain functional knowledge of the clusters, Spycone offers GSEApy [18] and NEASE [19] for gene set enrichment analysis. The former conducts classical enrichment analysis for multiple ontologies and pathway databases [20].…”
Section: Clustering Analysis For Identifying Co-spliced Genesmentioning
confidence: 99%
“…Gene set enrichment method is performed using Fisher's exact test. NEASE [19] is an enrichment method for co-regulated alternative exons. We used NEASE with KEGG and Reactome pathways.…”
Section: Gene Set Enrichment and Network Analysismentioning
confidence: 99%